Uji Efektivitas Ekstrak Paku Pedang (Nephrolepis exaltata) Terhadap Pertumbuhan Jamur Candida albicans - Ngadiani; Diana Mey Merlina (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2020)
Plant swords (Nephrolepis exaltata) are ferns in the Lomariopsidaceae tribe which are easily found on the banks of rivers, cliffs, and contain flavonoids and alkaloids that can inhibit the growth of albicans candida fungi. This study aims to determine the effectiveness of Sword nail extract (Nephrolepis exaltata) on the growth of albicans candida fungi. This research is a quantitative laboratory experimental type using a completely randomized design (RAL) with 4 different treatment groups, 1 negative control (pz sterile) and 1 positive control (ketocenazole). The parameters observed were the number of colonies (CFU) and the average area of ​​the inhibition zone (mm). The data was analyzed using SPSS software using one way ANOVA analysis which was then followed by a test using DMRT. The results showed that all concentrations differed from the negative controls, while the extract concentration of 1000 ppm compared to the positive controls had no difference. Sword nail extract (Nephrolepis exaltata) has an influence on the growth of candida albicans mushrooms, namely the number of colonies of 6.78 CFU (6x106) at a concentration of 1000 ppm and inhibition zone 33.10 mm at a concentration of 1000 ppm. Keywords : Candida albicans, Sword spikes (Nephrolepis exaltata), Inhibitory Zone, Colony Count.